2017
DOI: 10.1002/cdq.12082
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Undergraduate Student Retention in STEM Majors Based on Career Development Factors

Abstract: A research gap exists with regard to examining the influence of career interventions and career readiness assessments on student retention in college majors related to science, technology, engineering, and mathematics (STEM). To address this gap, the authors examined 3 variables as potential predictors of retention in STEMrelated majors: (a) a STEM-focused career planning intervention, (b) students' initial major declarations, and (c) changes in scores on a measure of career readiness. Results revealed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…In line with previous studies (Howard et al, 2011;Mau, 2003;Mau & Bikos, 2000;Padilla-Carmona & Martínez-García, 2013;Riegle-Crumb, Moore, & Ramos-Wada, 2011), gender and race were salient predictors of high school students' career aspirations and, as might be expected, remained strong predictors of STEM aspirations when all familial/parental, school/academic, and personal/psychological variables were taken into consideration. As with many prior studies (Belser, Prescod, Daire, Dagley, & Young, 2017;Fouad et al, 2010;Gnilka & Novakovic, 2017;Haynes & Jacobson, 2015;Raque-Bogdan et al, 2013; Schuster & Martiny, 2017), the female and minority students in our study experienced several barriers, such as lack of confidence, unfair treatment, discrimination, financial pressure, stereotypes, and biases, which help explain their lack of interest in STEM careers. Because female and minority students encounter many barriers in their educational and vocational pursuits, counselors working in school and other contexts should provide system-wide supports that increase female and minority academic, career, and personal/social success.…”
Section: Discussionsupporting
confidence: 61%
“…In line with previous studies (Howard et al, 2011;Mau, 2003;Mau & Bikos, 2000;Padilla-Carmona & Martínez-García, 2013;Riegle-Crumb, Moore, & Ramos-Wada, 2011), gender and race were salient predictors of high school students' career aspirations and, as might be expected, remained strong predictors of STEM aspirations when all familial/parental, school/academic, and personal/psychological variables were taken into consideration. As with many prior studies (Belser, Prescod, Daire, Dagley, & Young, 2017;Fouad et al, 2010;Gnilka & Novakovic, 2017;Haynes & Jacobson, 2015;Raque-Bogdan et al, 2013; Schuster & Martiny, 2017), the female and minority students in our study experienced several barriers, such as lack of confidence, unfair treatment, discrimination, financial pressure, stereotypes, and biases, which help explain their lack of interest in STEM careers. Because female and minority students encounter many barriers in their educational and vocational pursuits, counselors working in school and other contexts should provide system-wide supports that increase female and minority academic, career, and personal/social success.…”
Section: Discussionsupporting
confidence: 61%
“…At the end of the semester, the career planning students’ CTI scores significantly decreased, but the STEM‐declared students reported lower CTI posttest scores than the career planning students. Belser et al (2017) also found that reductions in negative career thinking during the first semester of college increased students’ odds of being in a STEM major in their second year of college. Beyond these studies, researchers have largely overlooked structured career planning within undergraduate STEM initiatives.…”
Section: Career Planning and Negative Career Thinkingmentioning
confidence: 98%
“…Such programs are tasked with addressing underrepresentation of women and ethnic minorities in STEM fields (Chen, 2013). Career planning courses demonstrate efficacy for general undergraduate populations (Osborn, Howard, & Leierer, 2007; Reardon, Melvin, McClain, Peterson, & Bowman, 2015), but researchers have less frequently applied them to STEM‐specific populations (Belser, Prescod, Daire, Dagley, & Young, 2017; Prescod, Daire, Young, Dagley, & Georgiopoulos, in press). The present study evaluated the influence of a STEM‐focused career planning course on undergraduates’ negative career thinking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating career development interventions aids in career exploration within a particular discipline, provides clarity in career choice, and leads to less commitment anxiety about that choice (Scott & Ciani, 2008). Including career development interventions can also help increase retention from freshman to sophomore year in college (Belser, Prescod, Daire, Dagley, & Young, 2017).…”
mentioning
confidence: 99%